OPTIMASI REKONFIGURASI JARINGAN DISTRIBUSI RADIAL UNTUK MEMINIMALKAN RUGI JARINGAN MENGGUNAKAN METODE SIMPLE BRANCH EXCHANGE - Yoakim Simamora; Sigit Sukmajati; Rio Afrianda (Sekolah Tinggi Teknik PLN, 2018)
The increasing electric energy consumption must be balanced with good electricity network quality. To overcome this, we need a distribution network reconfiguration. Reconfiguration in power distribution network is done to improve power distribution network quality. Problem that exist in the radial distribution network is power losses. To minimize the power losses can be overcome by compensating capacitor. Done by determining the location of capacitors in distribution networks. With that the capacitor compensates the distribution network is more effective and efficient in distributing power. In this research discusses the network reconfiguration using simple branch exchange method to reduce power losses in radial distribution networks . Plant that used in this final project is IEEE 33 bus feeders. Simple branch exchange method is a kind of heuristic method . It works by selecting the order of the loop is done for distribution networks reconfiguration. Simulation results show that the use of a simple branch exchange method for reconfiguring network can reduce energy loss by 63,4677 kW. From the simulation results using the distribution system IEEE 33 bus feeders, showed that the decrease of energy losses from 202,6845 kW become 139,2168 kW.